AKTIVITAS SEKTOR INFORMAL PADA MALAM HARI ( Studi Kasus Pembeli dan Pedagang Jagung Bakar Di Jalan Naga Sakti Stadion Utama Riau Pekanbaru ) - Marito Manurung; T. Romy Marnelly (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2017)
This Research is being conduct in Jalan Naga Sakti Stadion Utama Riau Pekanbaru with purpose of gaining an information about the informal sector at the end of the day. The problems are (1) How is a profile of a street roasted corn seller in Jalan Naga Sakti, Pekanbaru Riau ? (2) How is the behavior of roasted corn visitor in Jalan Naga Sakti Pekanbaru Riau? The title of this research is